Structural morphology and in vitro toxicity studies of nano- and micro-sized zinc oxide structures. Issue 1 (March 2015) - Ann, Ling Chuo; Mahmud, Shahrom; Seeni, Azman; Bakhori, Siti Khadijah Mohd; Sirelkhatim, Amna; Mohamad, Dasmawati; Hasan, Habsah
Graphical abstract: Highlights: Different particle sizes and morphologies of ZnO structures were identified. Increasing the concentration of ZnO induced higher toxicity towards cell lines. Toxic effect of nano-sized ZnO structures was due to higher release of zinc ions. Micro-sized ZnO samples had toxicity limits of 0.3 mM at most. Abstract: The structural morphology and in vitro toxicity of nano- and micro-sized ZnO structures were investigated. All the ZnO samples were characterized to determine their morphologies, particle sizes, structures and optical bandgaps. Transmission electron microscopy and field-emission scanning electron microscopy results revealed that the morphologies of nano-sized ZnO-N1 and ZnO-N2 samples consisted of spherical and irregularly-shaped particles, respectively. The corresponding particle sizes were 20–40 nm and 50–80 nm, respectively. The morphologies of micro-sized ZnO-M1 and ZnO-M2 samples were found to be mostly rod-structures and plate-structures, respectively. Rod diameters were 40–100 nm whereas plate widths were 50–150 nm. ZnO-N1 had the highest toxicity towards the cells, causing the cell viability to be less than 70% for all concentration ranges. This phenomenon was due to the small particle size and release of zinc ions. Micro-sized ZnO-M1 and ZnO-M2 samples had toxicity limits of 0.3 mM at most.